IDM : Sustaining Legacy, Creating a Niche - Joshi, Mahesh Chandra; Bhatia, Richa (AMC Indian Journal of Entrepreneurship, 2018)
The origin of the Indian sports industry can be associated with Sialkot which is now in Pakistan. It was known for its sports goods production before partition. Now the export products from thereÂ are sports goods, martial art equipments,Â leather products, and sports wear. IDM is a family oriented business firm which originated in Sialkot before partition. This firm manufactures and exports sports goods and equipments. This firm prefers to operate in niche markets by customizing the products.